Disability studies after the ontological turn: a return to the material world and material bodies without a return to essentialism - Feely, Michael (Disability & Society, 2016)
Over recent decades, poststructuralist theories have allowed critical disability scholars to challenge essentialist understandings of the human species and to contest discourses which divide humans into ‘normal’/‘impaired’ subjects with respect to a wide – and ever expanding – range of corporeal and cognitive traits. For critics, however, these theories are deeply flawed. By focusing primarily on language, poststructuralism shifts our critical attention away from the often harsh material realities of life for disabled people. This has led some to turn to critical realism and to effectively re-essentialise impairment. In this article, I wish to consider an alternative approach. I suggest that the recent ‘ontological turn’ in social theory has seen the emergence of new-materialist approaches – including Deleuze and Guattari’s ontology of assemblage and methodology of assemblage analysis – which allow us to consider disability as a material phenomenon without a return to essentialism.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; approches et analyses; corps; cours; discipline; féminisme matérialiste; histoire et politique; humaines; ontologie; philosophie; post-structuralisme; premier cycle; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; thématiques; études critiques du handicap

Manifestly Haraway - Haraway, Donna Jeanne (Posthumanities, 2016)
"Electrifying, provocative, and controversial when first published thirty years ago, Donna Haraway's "Cyborg Manifesto" is even more relevant today, when the divisions that she so eloquently challenges--of human and machine but also of gender, class, race, ethnicity, sexuality, and location--are increasingly complex. The subsequent "Companion Species Manifesto," which further questions the human-nonhuman disjunction, is no less urgently needed in our time of environmental crisis and profound polarization. Manifestly Haraway brings together these momentous manifestos to expose the continuity and ramifying force of Haraway's thought, whose significance emerges with engaging immediacy in a sustained conversation between the author and her long-term friend and colleague Cary Wolfe. Reading cyborgs and companion species through and with each other, Haraway and Wolfe join in a wide-ranging exchange on the history and meaning of the manifestos in the context of biopolitics, feminism, Marxism, human-nonhuman relationships, making kin, literary tropes, material semiotics, the negative way of knowing, secular Catholicism, and more. The conversation ends by revealing the early stages of Haraway's "Chthulucene Manifesto," in tension with the teleologies of the doleful Anthropocene and the exterminationist Capitalocene. Deeply dedicated to a diverse and robust earthly flourishing, Manifestly Haraway promises to reignite needed discussion in and out of the academy about biologies, technologies, histories, and still possible futures."-- Provided by publisher.
Keywords: LGBTQIA2+; animaux de compagnie; approches et analyses; chien; corps; cours; cyberféminisme; cyborg; discipline; discours dominant; identités LGBTQIA2+; lit4700; philosophie; point de vue situé; premier cycle; relations humains/animaux; ressource en ligne; sciences humaines; systèmes d'oppressions; technologie; thématiques

Des sexes innombrables: le genre à l'épreuve de la biologie - Hoquet, Thierry (Science ouverte, 2016)
Combient y-at-il de sexes? "Deux!", répond l'opinion. "Deux" répond la science. Heureuse concordance : c'est donc que l'opinion a raison, conclura-t-on. Mais est-on si certain que l'opinion et la science disent, sur la question du sexe, la même chose? Quand l'opinion affirme qu'il y a deux sexes, elle soutient qu'il existe, dans chaque espèce, deux types d'individus et seulement deux. Il y aurait alors le masculin et le féminin. Mais quand la science avance qu'il y a deux sexes, que vise-t-elle ? Quelle est, pour un biologiste, la signification des termes "mâle" et "femelle" ? En tentant de compter les sexes, on doit bientôt se risquer à distinguer le normal du pathologique.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; corps; cours; discipline; europe; france; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; régions géographiques; sciences humaines; sexe biologique; sexisme; sexualité; systèmes d'oppressions; thématiques